Mix Fertilizer “BiTrichompos” Inhibition Ability against Bacterial Wilt Disease, Ralstonia solanacearum, in Chili Plants (Capsicum annuum L.) - Ambar, Abdul Azis; Fahriani, Nur; Ilmi, Nur (Jurnal Perlindungan Tanaman Indonesia, 2025)
Chili production is hindered by bacterial wilt disease caused by Ralstonia solanacearum. Application of BiTrichompos can be an alternative control method of bacterial wilt diseases. BiTrichompos is an organic fertilizer derived from the secondary metabolism of Fusarium oxysporum and Trichoderma sp dissolved in rice washing water (leri). Secondary metabolism and Trichoderma sp. have been reported to be able to suppress plant disease causing pathogens. The purpose of this study is to evaluate BiTrichompos ability to manage bacterial wilt disease (Ralstonia solanacearum) and growth promoting effects on chili plants (Capsicum annuum L.). This research was conducted at Screen House Harzianum Parepare City, using a Completely Randomized Design with 4 treatments, namely A0 (control), A1 (5 mL of BiTrichompos/plant), A2 (10 mL BiTrichompos/plant), A3 (15 mL BiTrichompos/plant), and each treatment was repeated 5 times. Each replicated consisted of 3 plants totaling in 60 experimental units. Observations were made in the first week after planting and continued weekly for 7 weeks. Results showed that treatment A3 resulted in lowest bacterial wilt disease intensity of 31.53%, while to control resulted in 39.15%. Highest average fruit number and weight resulted from treatment A2, where fruit numbers averaged at 6.75 and total fruit weight was 29.57 g. Highest average root length of chili plants was also shown A2 (46 cm).